DNA sequence of the D-serine deaminase activator gene dsdC. - Palchaudhuri, S (1988)
We have determined the DNA sequence of dsdC, the gene that encodes the D-serine deaminase activator protein of Escherichia coli K-12. The sequence contains a single open reading frame that terminates in a UGA codon. One the basis of the size of the protein, 33 kilodaltons, and the amino acid sequence encoded by the open reading frame, we identified a likely translation initiation codon 731 base pairs upstream of the translation initiation codon for the divergently transcribed D-serine deaminase gene. There is a broad range of codon usage, not surprising in view of the weak expression of the gene. The N-terminal two-thirds of the activator is arginine-lysine rich and quite polar; the remainder is more neutral. The segment of the protein that seems most likely to have potential to form the helix-turn-helix structure characteristic of DNA-regulatory proteins is located near the end of the polar region. The protein contains a region with significant homology to lambda attB.